Penjor Galungan Sebuah Seni Religius - I Ketut Wartayasa; Komang Heriyanti (Jnanasidanta, 2020)
Art in a religious activity is very necessary, because art is an expression of the beauty of a people who is presented to Ida Sang Hyang Widhi Wasa. The Hindu community in Bali in various religious rituals emphasizes the value of art. One of them is the art of penjor which is used on Galungan Day. Penjor is a religious ceremony equipment for Hindus, so penjor is a part of religious art that contains sacred symbols in the materials used. Penjor is a decoration made of bamboo (from base to tip). Penjor religiously is a means of ceremony in celebrating Galungan and is a symbol of the mountain that provides safety and prosperity. Penjor is plugged in front of the house the day before Galungan Day, namely Penampahan Galungan. Installing penjor aims to create a sense of devotion and as an expression of our gratitude for the prosperity given by Ida Sang Hyang Widhi Wasa. The curved bamboo is a depiction of the highest mountain as a sacred place. Making penjor for ceremonies requires certain conditions, and is in accordance with religious literature, so that it is not just as decorative. Penjor is also a symbol of expression of gratitude to the earth or nature for providing a place to live and human welfare and in order to create peace and human welfare to achieve the victory of dharma against adharma.